E-learning Trends in English Educational Research: A Systematic Literature Review - Sukarton, Sukarton; Sulistyaningrum, Siti Drivoka (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research examines the trends in e-learning in English education in 2021 using a systematic literature review with content analysis. The study used a sample of 30 undergraduate students from 1992 and Google Scholar, with data from Crossref and Google Scholar. The research found that the e-learning trend is expected to be strong in 2021, with most publications being journal articles and using qualitative instruments like questionnaires. The application used for e-learning is Zoom, and the findings are generally supportive or positive.